2021
DOI: 10.1159/000517393
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Tumor Burden in Patients with Intermediate-Stage Hepatocellular Carcinoma: The Seven-Eleven Criteria

Abstract: <b><i>Background and Aims:</i></b> For patients with intermediate-stage hepatocellular carcinoma (HCC), the definition of high tumor burden remains controversial. This study aimed to compare the prognostic value of different criteria of tumor burden in patients with intermediate-stage HCC undergoing transarterial chemoembolization (TACE). <b><i>Methods:</i></b> From 2007 to 2019, 632 treatment-naive patients with intermediate-stage HCC undergoing TACE were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 31 publications
(44 reference statements)
4
40
0
Order By: Relevance
“…Furthermore, compared to that study, our cohort had considerably lower initial albumin levels and higher bilirubin levels, which indicated poor liver function. Similarly, in the initial reports on SAT and SEC, viral liver disease was the most common etiology, and liver function was considerably better in those cohorts than in our study cohort ( 13 , 20 ). In the original study on the SAT, the score outperformed the BCLC classification and the ALBI score in predictive ability.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, compared to that study, our cohort had considerably lower initial albumin levels and higher bilirubin levels, which indicated poor liver function. Similarly, in the initial reports on SAT and SEC, viral liver disease was the most common etiology, and liver function was considerably better in those cohorts than in our study cohort ( 13 , 20 ). In the original study on the SAT, the score outperformed the BCLC classification and the ALBI score in predictive ability.…”
Section: Discussionsupporting
confidence: 81%
“…Standardized cut-offs for the laboratory parameters were derived from our laboratory database. Cut-off values for TBS, SAT and SEC were adopted from the original publications ( 13 , 19 , 20 ). The distributions of patients, according to TBS SAT and SEC, were compared with the Chi-Square test for categorial variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent ALBI-TAE model suggested that up-to-eleven criteria is more discriminative than up-to-seven criteria to predict survival after TACE [19,21], whereas six-twelve criteria can stratify recommended TACE candidates [22]. Most recently, we proposed seven-eleven criteria to redefine tumor burden, which can predict radiologic response and survival in HCC patients undergoing TACE [33]. Taking together, high tumor burden is agreed to be an important parameter to select TACE unsuitable patients [13,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…During procedure, all target tumors were assessed by decreased antegrade tumor-feeding arterial flow. The embolization endpoint was reduced or no tumor stain along with subjective angiographic chemoembolization endpoint levels 2 and 3 [33].…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%